Feeling pressured by health prevention campaigns as a motivational force: Examining the role of visual and verbal mode design features. Issue 4 (2nd October 2022) - Möri, Michelle; Siegenthaler, Perina; Fahr, Andreas
Abstract: This research examines the influence of address style (direct, no address) and narrative voice (first-person, third-person) on the feeling of being pressured by a public service announcement about work stress in two sequential studies. The results of a choice-based conjoint analysis show that persuasive messages designed with a first-person narrative voice and direct address tend to pressure recipients. Results of a between-subjects online experiment suggest that this feeling increases subjects' behavioral intentions to prevent stress when people interact parasocially with the displayed character. Both direct address and first-person narrative voice led directly to reduced behavioral intention to prevent stress.